Post-Growth and Post-Extractivism: Two Sides of the Same Cultural Transformation (Alternautas, 2022)
Mainstream thinking – embedded within capitalist globalisation – leads us to accept the impossibility to imagine an economy that does not promote growth, as much as a world without oil, mining and agribusiness is impossible. Within this mainstream thinking, we can find people from every political stance, from neoliberals to socialists. Reality, however, is that we must overcome such views, that is the great task of this moment. On the one hand, we must rethink the question of economic growth, and free ourselves from its shackles before we enter into a global socio-environmental debacle with unforeseeable consequences. On the other, it is increasingly urgent to move from an extractivist perspective focused on the demands of capital, towards a view that prioritises a dignified life to its fullest extent and enables the construction of structurally democratic societies.